Características del desempleo juvenil en chile. Aplicación econométrica en base encuesta de caracterización socioeconómica nacional, casen 2015 (2020)
A classic explanation of unemployment is that it relates to economic cycles and shortterm demands of the labor market. In quantitative terms, in Chile the unemployment rate for young people doubles the general population, from which it can be interpreted that they are just beginning a career and, therefore, are less “employable” than adults. However, not all the characteristics that positively influence “activate” this phenomenon in Chile are known. Therefore, it is worth asking: what affects a young person being unemployed? Or are there differences between young people and adults who belong to the same national workforce? The present study tries to explore beyond a macroeconomic vision of unemployment, through an econometric exercise that evaluates socioeconomic characteristics that could influence youth unemployment in Chile. Using the National Socioeconomic Characterization Survey, Casen 2015, the main findings were that, youth unemployment is most strongly characterized in low-income and vulnerable households, in young women, in urban regions and sectors with the presence of some degree of poverty and , the most interesting thing is that it is possible to demonstrate the positive influence in the use of “contact networks” within the daily circles that people have.